Extrected principles and implications from the International Center for Aquatic research annual 1991-1992 - Rushall, B. S.
Adapted from NSWIMMING Coaching Science Bulletin: Volume 1 Number 5 - November, 1992. The purpose of this Bulletin is to highlight the major principles from each study in the 1991-92 Annual and explain their implications for coaching. It is the second issue devoted to the work conducted at ICAR in its initial years. Content: PHYSIOLOGICAL STUDIES, TRAINING RESPONSES AND ADAPTATIONS, BIOMECHANICAL STUDIES, NUTRITIONAL STUDIES.